2020
DOI: 10.11591/eei.v9i6.2235
|View full text |Cite
|
Sign up to set email alerts
|

Mobile augmented reality using 3D ruler in a robotic educational module to promote STEM learning

Abstract: Robotics education is gaining popularity among school children in line with the government desire to promote creative thinking in students through STEM based activities. However, the robots for educational games are usually made up of components and its description is usually one-way and static. Additionally, students find it difficult to visualize distances from robot movements when playing educational robotic games. Augmented reality (AR) technology is a viable tool to connect between in-context information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…AR can be applied in distance learning (Ahied et al, 2020;Altinpulluk et al, 2020;Faregh & Sisi, 2020) as well as VR (Fauville et al, 2021;Georgieva-Tsaneva & Serbezova, 2020;Harfouche & Nakhle, 2020;McFaul & FitzGerald, 2020). Several studies have also suggested that AR and VR technology can be used in STEM learning (Christopoulos et al, 2020;Nordin et al, 2020;Petrov & Atanasova, 2020;Yildrim et al, 2020;Wahyu et al, 2020). Thus, it is necessary to train AR and VR skills for both teachers and prospective teachers so that they can continue to carry out STEM learning during the COVID-19 pandemic in order to create quality education.…”
Section: Charting the Datamentioning
confidence: 99%
“…AR can be applied in distance learning (Ahied et al, 2020;Altinpulluk et al, 2020;Faregh & Sisi, 2020) as well as VR (Fauville et al, 2021;Georgieva-Tsaneva & Serbezova, 2020;Harfouche & Nakhle, 2020;McFaul & FitzGerald, 2020). Several studies have also suggested that AR and VR technology can be used in STEM learning (Christopoulos et al, 2020;Nordin et al, 2020;Petrov & Atanasova, 2020;Yildrim et al, 2020;Wahyu et al, 2020). Thus, it is necessary to train AR and VR skills for both teachers and prospective teachers so that they can continue to carry out STEM learning during the COVID-19 pandemic in order to create quality education.…”
Section: Charting the Datamentioning
confidence: 99%
“…Good communication between the teacher and the student represents one of the pillars on which the educational experience rests, regardless of whether students and teachers coincide in the same time and space, referring to the new virtual teaching-learning context. As indicated by [41]- [43] in teaching, a good teacher is needed with qualities such as: responsibility, flexibility, concern, creativity, dedication, communication and empathy, it is also important to indicate that virtual teaching-learning spaces require new Roles of the teacher, who must become a facilitator, teaching how to use computer tools, creating habits and skills in managing the search, selection and treatment of information. The principle to follow in the use of technological resources is to adapt technological tools to teaching, not teaching to them.…”
Section: Resultsmentioning
confidence: 99%
“…When the camera phone has tracked the marker, digital information corresponding to the name of the food in Malay which is "Mi goreng" will be displayed on the mobile screen. AR provides simulated access to learning methods and has proved to be an effective 3D visualisation technology in educational areas [17,18]. Ali and Azmi [12] investigated the use of AR for Malay language learning by developing a MAR Malay language application for international students to learn the language.…”
Section: B Mobile Augmented Reality Applicationsmentioning
confidence: 99%